IMPLEMENTASI ADMINISTRASI PERPAJAKAN BERBASIS DIGITAL DALAM PELAPORAN SPT PPh BADAN DI INDONESIA - Gabriel Gabriel; Penyang Penyang (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The development of information technology has encouraged the transformation of the tax administration system in Indonesia. The Directorate General of Taxes (DGT) has modernized tax administration through the implementation of digital systems to improve service effectiveness and taxpayer compliance. One form of this modernization is the implementation of the Coretax system, which integrates tax services into a single platform. This study aims to examine the implementation of digital-based tax administration in the reporting of Corporate Income Tax (CIT) Returns in Indonesia and the challenges encountered in its implementation. This study employs a descriptive qualitative approach using direct observation, active participation, and documentation methods. The results indicate that the implementation of a digital tax system has a positive impact on the efficiency of tax administration, particularly in tax reporting processes, tax task distribution, and taxpayer data management. However, the implementation of this system still faces several challenges, such as the transition of tax identity usage from Taxpayer Identification Number (NPWP) to National Identification Number (NIK), adaptation to the new system, and asset depreciation management in Corporate Income Tax reporting.